Respon konsumen muslim terhadap penggunaan produk P.T Unilever setelah mendukung LGBT - Alfi, Laila; Marliyah, Marliyah (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
LGBT is not justified in any religion, so that consumers as users of products issued by PT Unilever which officially announces support for LGBT, especially Muslim consumers, feel disappointed with the company's support. Not a few consumers also want to boycott and don't even buy and use them anymore, because according to some opinions LGBT is prohibited in Islam, even Allah clearly explains it in the Qur'an. However, some product users say that it is impossible or impossible to stop using the product again, because the products issued by this company have been used by the public for a long time and there is no doubt about the quality, even the price and how to get it are not difficult.